Interactions between β-arrestin proteins and the cytoskeletal system, and their relevance to neurodegenerative disorders - Szénási, Tibor; Turu, Gábor; Hunyady, László (Frontiers in Endocrinology, 2023)
β-arrestins, which have multiple cellular functions, were originally described as proteins that desensitize rhodopsin and other G protein-coupled receptors. The cytoskeletal system plays a role in various cellular processes, including intracellular transport, cell division, organization of organelles, and cell cycle. The interactome of β-arrestins contains the major proteins of the three main cytoskeletal systems: tubulins for microtubules, actins for the actin filaments, and vimentin for intermediate filaments. β-arrestins bind to microtubules and regulate their activity by recruiting signaling proteins to them and interact with assembly proteins that regulate the actin cytoskeleton and the intermediate filaments. Altered regulation of the cytoskeletal system plays an important role in the development of Alzheimer’s and Parkinson's disease, and other neurodegenerative diseases. Thus, β-arrestins, which interact with the cytoskeleton, were implicated in the pathogenesis progression of these diseases, and are potentially drugable targets for the treatment of neurodegenerative disorders in the future.